Coordination of Actors in the Implementation of Lusi Island Tourism Development in Kedungpandan Village, Jabon District, Sidoarjo Regency - Rodiyah, Isnaini; Mursyidah, Lailul; U.B, Ahmad Riyadh (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2022)
This study aims to analyze and describe the coordination of actors in the implementation of Lusi Island tourism development in Kedungpandan Village, Jabon District, Sidoarjo Regency. Data collection techniques were conducted by interview, observation, and documentation. The data analysis technique uses an interactive analysis model proposed by Miles and Huberman, consisting of four components, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the coordination of actors in the implementation of Lusi Island tourism development in Kedungpan Village and Jabon District, Sidoarjo Regency was carried out by interactive dialogue communication between actors, communication via WhatsApp, and holding exhibitions. Coordination and promotion are also carried out online. Comprehensive information on the leadership in the development of Lusi Island tourism is shown by the party who scheduled the meeting, namely Pokdarwis through public relations.